The features of the implementation of the state policy in the field of information society development in the Republic of Azerbaijan - B. G. Koybaev; Yu. V. Usova; Z. T. Zoloeva (Современная наука и инновации, 2023)
The article analyzes the modern state policy of Azerbaijan in the field of information society development and the mechanisms of its implementation. The development of the information society is one of the main tasks of the country, since the level of its development largely depends on the level of economic power and its place in the geopolitical arena. All this requires the implementation of a state policy aimed at its development. The main objectives of the state information policy are the implementation of activities to modernize the information and communication infrastructure; the implementation of measures aimed at the overall development of information technologies; the implementation of measures to enhance the use of information and communication technologies by citizens; the formation of effective legal frameworks accompanying the implementation of state policy. In addition, given that in modern conditions, the development of the information society is accompanied by the active development of digital technologies, the tasks of state policy in this area include the development of digital technologies, the development of citizens' skills to use them, ensuring information security. The expansion of the circulation and exchange of information in society with the use of new technologies has significantly enriched information policy, which is one of the important elements of democratic progress. The further development of a stable political system has opened a new stage in the political and economic development of the country. According to the authors, the information policy in Azerbaijan, including the state information policy, is currently in the period of its formation.